3D Printing with Polymer Composites Materials,Processes and Applications—A Review - Pandey, Rohit (Recent Advances in Mechanical Engineering, 2024)
One of the most interesting and revolutionary production options currently available is 3D Printing, a rapidly developing technology. In recent years, this technology has attracted a lot of attention and achieved international renown. The focus of study continues to be on technological developments, notably in the field of material science, especially in light of potential future developments. Due to their mass customisation, design freedom, capacity to print complicated 3D structures, and quick prototyping, 3D Printing techniques are used to manufacture innovative multifunctional polymer composites, and structural characteristics. For a wide range of engineering and construction applications, composite or reinforced materials, particularly those in the polymer class, are becoming more and more common. They have scientific uses because of their outstanding physical, chemical, mechanical. This paper discusses the development of 3D printing technologies for matrix composite materials with excellent qualities and their uses in the industries of electronics, aerospace, automotive, and biomedical. An extensive introduction of additive manufacturing (AM) methods highlights fused deposition modelling (FDM), powder-liquid 3D printing (PLP), selective laser sintering (SLS), stereolithography (SLA), digital light processing (DLP), and robocasting. Discussion is held regarding how various filler additives, reinforcing fibres, nanoparticles, and ceramic polymer composites behave during manufacture.
uGDX